Whole-body water mass and kidney function: a Mendelian randomization study - Wei, Xuejiao; Long, Mengtuan; Fan, Zhongyu; Hou, Yue; Yang, Liming; Qu, Zhihui; Du, Yujun (Frontiers in Endocrinology, 2024)
Background: The morbidity and mortality of chronic kidney disease (CKD) are increasing worldwide, making it a serious public health problem. Although a potential correlation between body water content and CKD progression has been suggested, the presence of a causal association remains uncertain. This study aimed to determine the causal effect of body water content on kidney function. Methods: Genome-wide association studies summary data sourced from UK Biobank were used to evaluate single-nucleotide polymorphisms (SNPs) associated with whole-body water mass (BWM). The summary statistics pertaining to kidney function were extracted from the CKDGen consortium. The primary kidney function outcome measures included estimated glomerular filtration rate (eGFR), albuminuria, CKD stages 3-5, and rapid progression to CKD (CKDi25). Two-sample Mendelian randomization (MR) analysis estimated a potential causal relationship between the BWM and kidney function. The inverse variance weighted MR method was used as the primary analysis, accompanied by several sensitive MR analyses. Results: The increase of BWM exhibited a correlation with a reduction in eGFR (β = -0.02; P = 6.95×10-16). Excluding 13 SNPs responsible for pleiotropy (P = 0.05), the increase of BWM was also associated with the decrease of the ratio of urinary albumin to creatinine (β = -0.16; P = 5.91×10-36). For each standard deviation increase in BWM, the risk of CKD stage 3-5 increases by 32% (OR, 1.32; 95% CI, 1.19-1.47; P = 1.43×10-7), and the risk of CKDi25 increases by 22% (OR, 1.22; 95% CI, 1.07-1.38; P = 0.002). Conclusions: The increase of BWM is associated with impaired kidney function. Proactively managing extracellular volume is of great significance in preventing the progression of CKD.